The Study Of EMA Effect On Modal Identification: A Review - Ramli, Mohd Irman; Nuawi, Mohd. Zaki; Abdullah, Shahrum; Mohammad Rasani, Mohammad Rasidi; Salleh, Mohd Shukor; Md Basar, Mohd Farriz (UTeM, 2017)
Modal Analysis is a common practice to define parameters of structure under scientific view. The properties that come along need to be enlightened so that every circumstance appeared can be tackled in proper manner. Experimental Modal Analysis (EMA) is a well-known procedure for determining modal parameters. The EMA is regarded as an ‘indoor tools’ to examine modal parameters. Meanwhile, Operational Modal Analysis (OMA) on the other hand acts as an ‘outdoor tools’, or operated at site. OMA tests in most engineering applications are not comparable to typical EMA tests. During a typical OMA test, the structure has different boundary conditions than the typical free-free conditions of an EMA test. Therefore, it can be expected that OMA results in many (or even most) engineering applications will show higher damping values than a free-free EMA test. Here, the EMA analysis method will be discussed. Modal parameters consist of mode shape, natural frequency and damping ratio. The study focused on performing mass change strategy via mass normalization of the displacement and strain mode shape occurred in strain EMA. By applying EMA, the mass-normalized displacement and strain mode shapes of the structures can be obtained, through matching the shapes which were calculated by FEM. The results were verified via classic EMA measurement method. One of the benefit of applying mass change strategy is other than obtaining the modal parameter, the strain mode shape parameter also possible to be determined. From the analysis, one can understand that the EMA has its own significant role in detecting modal appeared by mean of vibration. Thus, EMA proven to be a useful method to gain relevant data relating with mechanical properties characteristics other than strain such like stress, impact, tensile, elongation etc.